The diagnostic and therapeutic difficulties in management with pheochromocytoma in pregnancy – a review - Litwińczuk, Michał; Szydełko, Joanna; Szydełko, Magdalena (Journal of Education, Health and Sport, 2019)
Introduction: Pheochromocytoma (PCC) is a very rare and life-threatening condition in pregnancy. According to different data, it occurs in about 0,00002%-0,007% of pregnant women. The early diagnosis and the proper clinical management play a crucial role in decreasing maternal and fetal mortality. Aim of the study: This article summarizes the current knowledge about the management with PCC in pregnancy and presents the possible maternal and fetal outcomes.Description of knowledge: The review revealed, that manifestations of catecholamine-secreting tumors are similar to the most common hypertension-associated problems occurring in pregnancy, such as pre-eclampsia. That is why, timely diagnosis is essential for the mothers and fetuses’ survivals. Despite the fact, that the fetus is protected from influence of maternal overproduction of catecholamines due to the presence of placental enzymes activity, there is an enormous risk of spontaneous abortion, fetal growth restriction, premature delivery, when the optimal therapy will not be applied on time. The diagnosis is based on laboratory tests – determination of plasma and urine concentration of catecholamines and imaging tests to localize the tumor, from which only MRI, in 1st and 3rd trimester, and ultrasound examination can be safely used in pregnancy. The guidelines suggest surgical tumor removal as the treatment of choice for women with PCC in pregnancy. The 2nd trimester seems to be the best period for the surgery, however it can be performed only after 10-14 days of effective therapy with alfa- and beta-blockers. The review of literature revealed that, surgical tumor removal carried out before the end of 24. hbd, is safe both for mother and her fetus life.Conclusions: PCC is a great challenge, because of the extremely rare occurrence in pregnant women and serious complications due to the secretion of catecholamines, which may result in catecholamin crisis, increasing the risk of mortality. Nevertheless, there is still no clear consensus on PCC treatment and further researches are needed to develop the optimal management in this clinical condition.